2022
DOI: 10.3390/ijms23020976
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Multiple Genes and Complex Hormonal-Mediated Interactions with PEG during Adventitious Root Formation in Apple

Abstract: Adventitious root (AR) formation is a bottleneck for the mass propagation of apple rootstocks, and water stress severely restricts it. Different hormones and sugar signaling pathways in apple clones determine AR formation under water stress, but these are not entirely understood. To identify them, GL-3 stem cuttings were cultured on polyethylene glycol (PEG) treatment. The AR formation was dramatically decreased compared with the PEG-free control (CK) cuttings by increasing the endogenous contents of abscisic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In addition, the levels of GA3 were significantly higher in Garnem than in GF 677. A recent transcriptomic study on AR formation in apple rootstocks suggested that higher ABA and MeJA accumulation and lower GA3 levels could lead to AR inhibition [ 36 ]. Based on these results, it is tempting to speculate that a conserved hormonal balance could regulate AR formation in woody species and, as such, could be used as a bioindicator of rooting performance during rootstock breeding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levels of GA3 were significantly higher in Garnem than in GF 677. A recent transcriptomic study on AR formation in apple rootstocks suggested that higher ABA and MeJA accumulation and lower GA3 levels could lead to AR inhibition [ 36 ]. Based on these results, it is tempting to speculate that a conserved hormonal balance could regulate AR formation in woody species and, as such, could be used as a bioindicator of rooting performance during rootstock breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sugar content regulated the process of AR formation and sucrose AR numbers in apples (Pawlicki & Welander, 1995). In recent studies, starch and sucrose metabolism-related genes were activated by KCl and indole butyric acid treatments and promoted AR formation; in contrast, these were inhibited by drought and high nitrate stresses and led to severe defects in AR formation in apples (Li et al, 2018(Li et al, , 2022cTahir et al, 2021a;Zhang et al, 2021). Consistent with these observations, starch and sucrose metabolism-related genes were upregulated in WT_LN_vs_OE_LN and downregulated in OE_LN_v-s_OE_MN and WT_LN_vs_WT_MN microshoots (Supporting Information: Figure S14 and Table S12), which were highly correlated with their phenotypes (Figure 1).…”
Section: Sugar Signaling Mediated Ar Formationmentioning
confidence: 99%